Winning the Battle after Three Years of Suffering: A Case of a Refractory Pyoderma Gangrenosum Treatment Challenge - Ibrahim, Isra; Shereef, Hammam; Hashim, Ahmed; Habbal, Heba; Mahmood, Raai; Mohamed, Mohamed A. (Case Reports in Rheumatology, 2021)
Pyoderma gangrenosum is an uncommon inflammatory disorder characterized by neutrophilic infiltration of the skin. It can present as skin papules or pustules that progress into painful ulcers. 30–40% of the cases are associated with other systemic diseases such as inflammatory bowel diseases, rheumatoid arthritis, and proliferative hematological disorders. Uniquely, this condition has been associated with systemic lupus erythematosus (SLE). The rarity of this disorder poses a diagnostic and therapeutic challenge. We present a case of a 55-year-old female with a history of SLE and chronic right leg ulcer, presented with increased pain from the ulcer associated with a mild flare of her cutaneous lupus; examination revealed circumferential skin ulcer measuring about 25 cm extending around the right leg above the ankle with prominent fibrinous material and surrounding erythema. Blood work showed elevated WBC with neutrophilic predominance. Serology revealed a positive ANA, elevated RNP, smith, and SSA/Ro antibodies with normal anti-CCP level. Skin biopsy was taken, and it showed a diffuse neutrophilic and lymphocytic infiltrate consistent with the diagnosis of pyoderma gangrenosum. The patient was then treated with topical and systemic steroids and sequentially with dapsone, methotrexate, mycophenolate, and cyclosporine for over a two-year period but failed to show any improvement. Therefore, a trial of intravenous immunoglobulin (IVIG) therapy was attempted and produced a dramatic response after two-month infusions characterized by shrinking in the size of the ulcer and resolving pain. We believe that refractory PG poses a therapeutic challenge, and despite a lack of specific guidelines, IVIG can be attempted if initial suppressive treatment fails to show signs of improvement.